Intimacy and social capital on Facebook: Beyond the psychological perspective. (December 2016) - Lambert, Alex
Social capital has become a key concept in the study of social network sites such as Facebook. An influential body of literature has emerged which links the accumulation of social capital on Facebook to various psychological traits and depositions. There is a need to augment this work with a more critical, qualitative approach which recognises other key social and technological aspects of Facebook. Based on ethnographic research, I explore how the exchange of social capital on Facebook is significantly influenced by mobility, surveillance and norms of public intimacy. Facebook users must continually negotiate intimacy when claiming on social capital, and this involves a nascent set of social skills and digital literacies. I suggest the term 'intimacy capital' to conceptualise the way in which these skills are distributed unevenly in society, opening up a critical way of thinking about social capital and intimacy on Facebook.